Characteristics and adherence of the elderly to the management of hypertension treatment - Marlin Brigita; Hijrawati Hijrawati; Syaputra Artama (Jurnal Ilmiah Kesehatan Sandi Husada, 2023)
Hypertension is the main causative factor of cardiovascular disease, the leading cause of death in the world. Low adherence to treatment from people with hypertension is a concern at this time, especially in the elderly group. Non-compliance of patients in treatment management will impact uncontrolled blood pressure. Uncontrolled blood pressure for a long time can cause complications of hypertension. This study aims to identify and analyze the characteristics and compliance of the elderly with the management of hypertension treatment. Descriptive cross-sectional study design, determination of samples with consecutive sampling of 100 respondents included in the inclusion criteria. The study's results related to the level of knowledge of older people with adherence to treatment management (p = 0.083). It can be concluded that treatment is carried out if there are complaints about the sufferer, a rush of activity, and boredom due to long suffering from the disease. Therefore, it is essential always to provide education and treatment assistance for sufferers from health workers and families